The Effects of Land Use Change on Water Quality in the upper Berg - and Breede River catchments, Western Cape, South Africa - van Wyngaard, Zahn (University of the Witwatersrand, Johannesburg, 2024)
Pollution of surface water resources is gaining global attention due to increasing freshwater stress and scarcity. This study assessed how land use changes in the upper catchments of the Berg and Breede rivers affect water quality. Land Cover Data, covering a 22-year period, was prepared, categorised, and analysed. Land use classes include “natural”, “urban”, “agricultural”, “water bodies”, “mining” as well as “degraded land, bare rock, and soil”. Changes of these land use classes were analysed to establish their influence on water quality parameters such as electrical conductivity, pH, total nitrogen including ammonium, nitrate and nitrite, orthophosphate, and sulfate. In the Berg River catchment, urban, natural, water bodies and degraded land, bare rock, and soil increased while agricultural and mining decreased. In the Breede River catchment, urban, water bodies and degraded land, bare rock, and soil as well as mining increased while agricultural and natural decreased. In the Berg River catchment, Dissolved Inorganic Nitrogen (ammonium, nitrate and nitrite), as well as pH increased while electrical conductivity, sulfate, and orthophosphate decreased. In the Breede River catchment, ammonium and orthophosphate increased while a decrease in electrical conductivity, nitrate and nitrite, pH, and sulfate was noted. In the Berg River catchment, the following correlations, or relationships, were noted. Urban land was correlated with ammonium and sulfate; agricultural land was correlated with electrical conductivity and sulfate, natural land cover was correlated with electrical conductivity, orthophosphate, and sulfate. Water bodies were correlated with orthophosphate, sulfate, degraded land, bare rock, and soil was correlated with ammonium and mining was correlated with electrical conductivity, orthophosphate, and sulfate. In the Breede River catchment, urban land was correlated with ammonium and orthophosphate, agricultural land was correlated with nitrate and nitrite and pH, and natural land cover was correlated with electrical conductivity, ammonium, and sulfate. Water bodies were correlated with electrical conductivity, nitrate and nitrite, and sulfate, degraded land, bare rock, and soil were correlated with electrical conductivity, ammonium, orthophosphate, and sulfate, and mining was correlated with electrical conductivity, ammonium and sulfate. The study therefore recommends that we mitigate land use change impacts on water quality by enforcing strict land-use regulations, promote sustainable agricultural practices, protect riparian areas and wetlands, implement better stormwater and wastewater management, educate the public, and coordinate integrated water resource management efforts to reduce pollution of scarce surface water resources.
Research report submitted in partial fulfilment of the requirements for the degree of Masters in science (MSc), to the Faculty of Science, School of Animal, Plant, and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Water quality; Land use change; Environmental Impact; Land Use planning; Surface water; Pollution; UCTD; SDG-6: Clean water and sanitation; SDG-15: Life on land